PERTUMBUHAN DAN HASIL TANAMAN CABAI BESAR (Capsicum annuum L.) DENGAN PEMBERIAN MIKORIZA DAN MIKROORGANISME LOKAL BONGGOL DAN BATANG PISANG - Alvera Prihatini Dewi Nazari; Eliyani Eliyani; Mirza Akbar (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2022)
The research was conducted to find out the effect of interaction; mycorrhizal dosage; and local microorganisms of weevil and banana stems on the growth and yield of red chili. The experiment was conducted from February to June 2020 in Loa Bakung Village, Sungai Kunjang Subdistrict, Samarinda, arranged in a Randomized Complete Block Design consisting of two factors and replicated seven times. The first factor was mycorrhizal dose, consisting of four levels: 0; 5; 10; and 15 g plant-1. The second factor was the concentration of local microorganisms, consisting of four levels, namely: 0 mL L-1  (100% water);100; 200; and 300 mL L-1. The variables observed were an increase in plant height, number of branches, flowering age, fruiting age, number of fruit, fresh weight of fruit, dry weight of fruit, fruit diameter, and fruit length.  Data were analyzed by analysis of variance and continued by Duncan’s Multiple Range Test at a level of 5%.    The results showed that the interaction between mycorrhizae and MOL was significantly different on fresh fruit weight and fruit dry weight with the best treatment being 10 g mycorrhizal plant-1 and 200 ml MOL L-1 on fresh fruit weight and dry fruit weight, 303.14 and 36.86 g plant-1. The effect of mycorrhizae was significantly different on fresh fruit weight, fruit dry weight, fruit diameter, and fruit length, with the best dose being 10 g mycorrhizal plant-1, obtained fruit fresh weight 229.42 g and fruit dry weight 26.77 g. The effect of MOL was significantly different on the number of fruit, fruit fresh weight, fruit dry weight, fruit diameter, and fruit length, with the best concentration was 200 mL MOL L-1 obtained fresh fruit weight of 256.53 g and fruit dry weight 29.98 g.